The Mediating Role of Science Knowledge in Linking Digital Well-Being and Media Literacy to Critical Thinking Skills: A PLS-SEM Analysis - Andriani, Nike; Rosba, Evrialiani; Anggraini, Villia (Jurnal Pendidikan MIPA, 2025)
This study aims to analyze the influence of digital well-being, knowledge of learning media, and teaching material satisfaction on students’ science knowledge and critical thinking skills through an integrative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through an online questionnaire administered to 366 respondents, followed by construct validity and reliability testing. The results show that digital well-being has a significant positive effect on science knowledge, but is nonsignificant and even tends to be negative in its relationship with critical thinking skills. In contrast, knowledge of learning media and satisfaction with teaching materials were found to have positive, significant effects on both science knowledge and critical thinking skills. In addition, scientific knowledge is an important predictor of critical thinking skills. Effect size analysis indicates that digital well-being, learning media knowledge, and teaching material satisfaction explain 32.7% of the variance in science knowledge (R² = 0.327). In comparison, satisfaction with science knowledge and teaching materials explains 25.6% of the variance in critical thinking skills (R² = 0.256), indicating a model with moderate predictive strength. These findings confirm that media literacy, satisfaction with teaching materials, and digital well-being work simultaneously to strengthen the foundation of science knowledge while promoting higher-order thinking skills. However, the influence of digital well-being on critical thinking is indirect. This study can serve as a reference for educators and policymakers in designing science learning strategies that balance technology use, strengthen media literacy, and provide relevant teaching materials. Keywords: digital well-being, knowledge of learning media, teaching materials satisfaction, science knowledge, critical thinking skills.